The Mechanisms of In Vitro Cytotoxicity of Mountain Tea, Sideritis scardica, against the C6 Glioma Cell Line - Jeremic, Ivica; Tadic, Vanja; Isakovic, Andjelka; Trajkovic, Vladimir; Markovic, Ivanka; Redzic, Zoran; Isakovic, Aleksandra (Planta Medica, 2013)
Sideritis scardica (mountain tea) is an endemic plant on the Balkan Peninsula traditionally used for treating different conditions, mainly of inflammatory nature. This study was aimed to examine the cytotoxic activity of different S. scardica extracts against the rat glioma C6 line and rat astrocytes in primary culture. The obtained data revealed that diethyl ether (extract 2) and ethyl acetate (extract 3) extracts of S. scardica exerted a cytotoxic effect on C6 rat glioma cells. Diethyl ether extract induced an increase in reactive oxygen species production, leading to apoptotic and autophagic cell death. Ethyl acetate extract induced G2 M cell cycle arrest and autophagy. None of the tested extracts was cytotoxic to rat astrocytes in primary culture. Cytotoxic effects of S. scardica extracts were, at least in part, mediated by their flavonoid constituents apigenin and luteolin that, when applied alone, induced cell cycle arrest, apoptosis, and autophagy.
Keywords: Sideritis scardica; Lamiaceae; apigenin; luteolin; C6 glioma cells; autophagy